The Phenomenon of Street Vendors in Public Spaces (Case Study: Tengku Amir Hamzah Stabat Square) - Luthfi, Irsanuddin; Fidyati; Karsono, Bambang (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2023)
Tengku Amir Hamzah Stabat Square is a public space that acts as a place to accommodate all community activities in Stabat District and its surroundings. The existence of the activities of the street vendors who occupy this public space has raised pros and cons. Street vendors not only interfere with the use of public spaces, but street vendors also provide social space and are able to attract people to gather and revive activities in public spaces. This study aims to reveal the characteristics and forming elements of public space applied by street vendors. This type of research is qualitative with data analysis using descriptive analysis method. Data collection was carried out in two stages, the first stage used the observation and documentation method, then the second stage used the interview method. The results of this study indicate that the profile characteristics of street vendors and elements forming a public space that are applied by street vendors are elements of comfort and image, access and linkage, uses and activity, and sociability. To create comfort and image elements, street vendors provide physical attributes such as benches/chairs, tables, shade, games and music. Its strategic location because it has proximity to the city's bustling centers really supports the elements of access and linkage. The uses and activities elements offered by traders are places to eat or drink, play, relax, and have recreation. Street vendors are able to accommodate elements of sociability such as observing the scenery, meeting friends, interacting with other people, and gathering with family, due to the variety of types of merchandise offered at relatively low prices.